(untitled) (INTERNATIONAL SCIENTIFIC E-CONFERENCE " INNOVATIVE TRENDS IN SCIENCE, PRACTICE AND EDUCATION" – Ankara, Turkey, 2024)
to study pathomorphological changes in myocardial structures in KMP. As material, cases of CMP autopsied in RPAM during 2011-2020 were obtained, and the autopsy report and medical history were studied. In KMP, heart failure suddenly developed in the right ventricle and left ventricle, cardialgia and angina pectoris; heart rhythm disturbances, often ventricular fibrillation, ventricular extrasystole and blockage of conduction paths were observed in some cases with thromboembolism. Histologically, the following types of pathomorphological changes were observed in the myocardium and endocardium in KMP, i.e. excessive growth of interstitial connective tissue, myxomatosis, lipomatosis developed in some places. Among the initial changes characteristic of KMP, the main ones were stretching of muscle fibers, i.e., thinning of muscle fibers, thinning of the transverse extension lines of cardiomyocytes, disintegration and homogenization, irregular arrangement of their nuclei, and deformation and dystrophy under the influence of surrounding changes.